Contrahemispheric Cortex Predicts Survival and Molecular Markers in Patients With Unilateral High-Grade Gliomas - Yuan, Taoyang; Ying, Jianyou; Zuo, Zhentao; Jin, Lu; Gui, Songbai; Gao, Zhixian; Li, Guilin; Wang, Rui; Zhang, Yazhuo; Li, Chuzhong (Frontiers in Oncology, 2020)
Background：Malignant high-grade gliomas are characterized by infiltration and destruction of surrounding brain tissue. Alterations of contrahemispheric brain structure and their roles in offer prognostically valuable information have not been investigated in high-grade gliomas. Methods: 153 patients with unilateral glioma (low-grade, n=77; high-grade, n=76) and 115 healthy controls were recruited and scanned with 3D T1 imaging. Gray matter (GM), white matter, and cerebrospinal fluid volume in contrahemisphere were examined. Correlation analysis, logistic regression and multivariate Cox's regression analysis were performed. Results: Contrahemispheric GM volume (CHGMV) significantly decreased in high-grade gliomas compared to healthy controls/low-grade gliomas (Bonferroni corrected, p < 0.05). CHGMV is significant correlation with WHO grade and contrast enhance volume (P < 0.05). In high-grade gliomas, binary logistic regression revealed that CHGMV can independently predict isocitrate dehydrogenase 1 (IDH1) and P53 mutation. Survival curves revealed patients with low CHGMV are presented with shorter OS compared to patients with high CHGMV (P = 0.001). Multivariate Cox's regression analysis disclosed that low CHGMV can independently predict unfavorable OS with hazard ratio 2.883 (p = 0.035). Conclusions: Atrophy of contrahemispheric cortex can be potentially used in clinical practice as imaging biomarker to predict survival and molecular markers for patients with unilateral high-grade gliomas.